Penerapan Dan Pelatihan Perpustakaan Digital Desa Cangkring Kabupaten Cirebon - Sandy Eka Permana; Ade Rizki Rinaldi; Mulyawan (CV. Multi Kreasi Media, 2023)
Community Engagement aims to implement and provide training related to the Digital Village Library in Cangkring Village, Cirebon Regency. This community engagement initiative strives to enhance access and utilization of digital information resources at the village level. Through a participatory and collaborative approach, this program involves various stakeholders including the local community, village government, and local educational institutions. The initial step involves a preliminary study to evaluate the existing conditions in Cangkring Village, including digital literacy, technological infrastructure, and the community's needs related to digital resources. Based on the findings of the Community Engagement, a platform and library management system suitable for the local context and needs were selected. Technological infrastructure was updated and the digital collection was enriched with various types of content, including e-books, journals, and educational materials. The training program is designed to enhance digital literacy and maximize the benefits of the digital library. This engagement also involves ongoing mentoring and guidance for library staff and community members regarding the management and utilization of the digital library. Continuous evaluation is conducted to monitor the usage and effectiveness of the program, relying on feedback from the community. The results of this program demonstrate a significant improvement in access and utilization of digital information resources in Cangkring Village. These findings positively contribute to the enhancement of digital literacy and education at the village level. This program also provides a foundation for similar efforts in neighboring villages, strengthening the role of the digital library as a center for learning.